Die Esthernovelle : vom Erzählten zur Erzählung : Studien zur Traditions- und Redaktionsgeschichte des Estherbuches - Kossmann, Ruth. (Supplements to Vetus Testamentum,, 2000)
In this book the author attempts to unravel the original narratives which underlie the biblical Book of Esther. She reconstructs the contents of three non-Jewish narratives: A wedding story, in which the foreign beauty (Esther) takes the place of the disobedient queen, and two court narratives, telling the story of the rivalry between two courtiers at the Persian court. In exilic and postexilic times these basic narratives were merged into one topical and literarily well developed narrative, which expressed the problems connected with Jewish life in the diaspora. The author shows that this text has been redactionally revised once more, in an attempt to adjust Palestinian Judaism to the Jewish communities that flourished in the diaspora. This redaction bears the hallmarks of Judaism's clash with Hellenised political forces; Purim emerges as a succesful defense.